Self-care behaviors among hypertension patients in U-Tapao Village, Mokhalan Subdistrict, Tha Sala District, Nakhon Si Thammarat Province - Mueang-U, Porawut; Waiyarat, Netimai; Kuesaeng, Tasana (Chalermkarnchana Academic Journal, 2022)
The purpose of this quantitative research was 1) to study self-care behaviors of patients with hypertension, 2) to study the relationship between self-care Knowledge, attitude, and behavior factors about hypertension and 3) to study the relationship between self-care behaviors and personal factors related to hypertension in U-Tapao Village. The sample consisted of 110 patients with hypertension in U-Tapao village area. The researcher used the SPSS program to interpret the research results from the test of the research data collection tool. The results showed that the self-care behavior of patients with hypertension was overall at a good level. Factors that affect self-care behavior of diabetic patients include.